Antibody-induced restriction of viral gene expression in measles encephalitis in rats. - Liebert, U G (1990)
After infection with the neurotropic CAM/RBH measles virus (MV) strain, newborn Lewis rats succumb to an acute necrotizing encephalopathy. Passive transfer of neutralizing monoclonal antibodies directed against MV hemagglutinin prevented this disease process. Instead, either an antibody-induced acute or subacute measles encephalitis developed after a prolonged incubation period with a restricted expression of MV structural proteins. The molecular biological analysis of MV gene expression in brain tissue of rats treated with MV-neutralizing antibodies revealed a transcriptional restriction of viral mRNAs, particularly for the envelope proteins, leading to a steep expression gradient. Based on in situ hybridization, it was concluded that the efficiency of transcription of viral genes at the single-cell level is reduced compared with that of controls. Passive immunization with monoclonal antibodies directed against other MV structural proteins proved to be ineffective. Similar results were obtained in MV-infected weanling Brown Norway rats. These rats developed a clinically silent encephalitis in the presence of high titers of neutralizing antibodies. In such animals, a pronounced attenuation of the viral gene transcription was observed. These findings indicated that neutralizing antibodies directed against a restricted set of specific antigenic sites on the viral hemagglutinin protein expressed on cell membranes exert a modulating effect on the viral gene expression at the level of transcription. This phenomenon contributes to the switch from the acute cytopathic effect to a persistent infection in the central nervous system.